Pre-Pulseless Takayasu Arteritis in a Child Represented With Prolonged Fever of Unknown Origin and Successful Management With Concomitant Mycophenolate Mofetil and Infliximab - Rabia Miray KIŞLA EKİNCİ,; Sibel BALCI,; Ferhat Can PİŞKİN,; Celal VARAN,; Sevcan ERDEM,; Mustafa YILMAZ, (Archives of Rheumatology, 2020)
Takayasu arteritis (TA) is classified as a large vessel vasculitis of predominantly aorta and its main branches, resulting in fibrosis and stenosis. Only a minority of TA patients are diagnosed in pre-stenosis phase when constitutional symptoms including fever, arthralgia, weight loss, headache, abdominal pain, and elevated acute phase reactants are dominant insidious characteristics. In this article, we present a 12-year-old female patient, who was referred to our department with a one-year history of low-grade fever, fatigue, and myalgia. Physical examination did not reveal pulse and blood pressure discrepancies between any extremities. Acute phase reactants were markedly elevated, and autoantibodies were negative. Magnetic resonance angiography (MRA) findings have confirmed TA diagnosis with prominent vessel wall thickening in the ascendant and abdominal aorta, focal ectasias and a thoracoabdominal fusiform aneurysm. As methotrexate and methylprednisolone treatment during three months was unsuccessful, infliximab was induced. During the next 12 months, patient had clinical improvement, but worsening of MRA findings and new onset of carotidynia forced us to switch methotrexate to mycophenolate mofetil. Six months later, laboratory and radiological remission were achieved. In conclusion, we report a challenge to diagnose pre-pulseless childhood-TA (c-TA) in the state of prolonged fever with no signs of vascular stenosis, systemic hypertension, pulses and blood pressure discrepancies, bruits and claudication. Therefore, we wish to discourse the importance of early diagnosis of TA since, to our knowledge, there are no studies investigating treatment success only in the early phases of c-TA.